An analytic network process approach for the election of green marketable products - Ratapol Wudhikarn (2018)
© 2015, Emerald Group Publishing Limited. Purpose – In this study, an optimal green product is selected from three newly developed ecological products and a non-environmentally friendly product. An analytic network process (ANP), used widely for multi-criteria decision making (MCDM), is applied to account for the tradeoff issues among the criteria (quality, cost and green issue) in the new green product selection processes. The paper aims to discuss these issues. Design/methodology/approach – This paper focuses on current social and consumer requirements. New product selection processes consider three major perspectives, i.e., quality, cost and environment, as criteria. The following two main methods are applied to respond to this multi-disciplinary issue: the eight quality dimensions proposed by Garvin are used to manage the quality issue, and a life cycle costing (LCC) method is applied for consideration of the cost and green issue. Therefore, the dependency issue among the criteria is considered, using a suitably selected method, the ANP method, and all the methods are applied to a real business, which produces roof tiles, for the delivery of a new optimal green product. Findings – An optimal environmentally friendly product does not overcome the existing toxic product of the focused company. The environmental performance is necessarily balanced by the quality and cost capabilities. Research limitations/implications – This paper focuses on the new product selection of roof tile products. The criteria or measuring indicators may be dissimilar, and cannot be applied to other products. Practical implications – The proposed approach can be applied to other manufacturing companies or services to allow decision makers to make better determinations for a comprehensive dependency problem. The managers can apply the proposed model to benchmark the considered products as well as to find the weaknesses of products. Originality/value – This method considers the relationship among quality, cost and environment for newly developed green products. The method produces better results than former MCDM studies which did not account for the dependency issue among the criteria.